Education in palliative and end-of-life care during medical training in pediatrics: scoping review protocol (Research, Society and Development, 2022)
Objective: To map the scientific knowledge on palliative and end-of-life care education aimed at physicians in pediatric training. Method: A scoping review protocol according to the JBI Institute method, registered in the Open Science Framework platform. Literature will be considered according to the inclusion criteria: education in palliative and end-of-life care (Concept) aimed at physicians (Population) in pediatric training (Context). Letters to the editor will be excluded. A detailed search strategy will be used for each database: MEDLINE/PubMed, COCHRANE, EMBASE, Biblioteca Virtual em Saúde, Scopus, Web of Science and Portal de Periódicos from Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES). Gray literature will be searched in the sources: Google Scholar, Biblioteca Digital Brasileira de Teses e Dissertações, Catálogo de Teses e Dissertações from CAPES. Two reviewers will screen the studies using Rayyan software through titles and abstracts, read the selected full texts and extract data from the included material. The evidence found will be synthesized according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) protocol.